Approach of Colorectal Surgeons to Lower Rectal Adenocarcinomas: Results from the Turkish Society of Colon and Rectal Surgery Database. - Sünter, Kaan; Koç, Mehmet Ali; Aytaç, Erman; Group, Turkish Colorectal Cancer Database Study (Turkish Journal of Colorectal Disease, 2025)
Aim This study aimed to analyze surgical preferences and outcomes among patients with lower rectal tumors in Türkiye using data from the national Colorectal Cancer Database of the Turkish Society of Colon and Rectal Surgery (TSCRS). Method A retrospective analysis was conducted on 158 patients with lower rectal tumors who underwent surgery between July 2018 and March 2022, with data prospectively collected from the TSCRS database. Variables included demographic characteristics, neoadjuvant therapy administration, surgical techniques, and postoperative outcomes. Results Among the 158 patients (mean age: 57.8 years; 58.2% men), 95.6% received neoadjuvant therapy. Approximately half the patients underwent open surgery, and the other half underwent minimally invasive surgery (MIS). The T-stage distribution differed significantly (p=0.009); early-stage cancers (stages I-II) were more frequently treated with MIS, whereas advanced stages (stages III-IV) were predominantly managed with open surgery. Conversion from laparoscopic to open surgery occurred in five patients (5.9%). Abdominoperineal resection was more common in patients who underwent open surgery. Hand-sewn anastomosis was performed more frequently in patients undergoing MIS. The operative time was longer for MIS than for open surgery (249±85 min vs. 169±52 min). The circumferential resection margin positivity rate was 3.2%, and tumor perforation occurred in 4.5% of cases. Conclusion The treatment of lower rectal cancer increasingly relies on a multidisciplinary approach integrating neoadjuvant therapies and diverse surgical techniques. Turkish surgeons adopt a tailored approach based on patient characteristics, leading to similar adoption rates for both surgical techniques. These findings highlight the dynamic and evolving nature of lower rectal cancer management, particularly in the context of neoadjuvant treatment strategies. Keywords:Low anterior resection, lower rectal cancer, minimally invasive surgery, multidisciplinary approach, neoadjuvant therapy: